Comment les étudiants se préparent-ils aux stages ? Ressources exploitées et choix stratégiques - Deprit, Agnès; Van Nieuwenhoven, Catherine (Canadian Journal of Education/Revue canadienne de l'éducation, 2018)
While preparing for an internship, students expect to be supported (Caron & Portelance, 2017) in their articulation of both theory and practice. Qualitative exploratory research with a comprehensive focus (Van der Maren, 1996) has been conducted to identify the strategies and resources that students use. Four female primary school teacher trainees were invited to complete a daily log and participate in a semi-structured interview. The results of the analysis emphasize the importance that students place on the knowledge gained from experience (Vause, 2011).